'Disorderly conduct': on the unruly rules of public communication in social network sites. (3rd June 2013) - WAGNER, ELKE; STEMPFHUBER, MARTIN
Abstract In this article, we examine typical styles and practices of public communication on social network sites (SNSs) in order to confront the traditional concept of publics as machines for creating order. Through an ethnographic case study of the SNS Facebook, we show how indeterminacy, ambiguity and constant irritation, rather than arguments or reason, produce the communicative order. A decidedly disorderly style of communication and connectivity emerges. Indeterminacy, from our point of view, is a solution to the problem of speaking privately in public and to an indefinite audience. We use these findings to problematize the insights of network theory and Niklas Luhmann's systems theory that only out of noise can we generate order – we can also generate it through noise. Since order undermines itself through the creation of ambiguous communicative possibilities, a new kind of public sphere is created.